When fans travel: Determinants and effects of away support in football - Joschka Flintz (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
This study examines the determinants of away fan attendance in Germany's top three football divisions over six seasons and assesses its impact on match outcomes. The analysis reveals that, after conditioning on home and away teams, distance and kick-off time are the most important predictors of away fan turnout. Moreover, away support is found to have a statistically significant positive effect on team performance: an additional 1,000 away fans is associated with a 4.6% to 7.5% increase in the probability of the away team winning or drawing the match. These findings suggest that league organizers should consider fan logistics and the potential influence of away fan presence when scheduling fixtures, in order to maintain sporting equity. At the club level, the results underscore the value of fostering fan engagement and indicate that strategies aimed at increasing away attendance may contribute to improved sporting outcomes. – – Diese Studie untersucht die Determinanten der Auswärtsfanbeteiligung in den drei höchsten deutschen Fußballligen über sechs Spielzeiten hinweg und bewertet deren Auswirkungen auf die Spielergebnisse. Die Analyse zeigt, dass nach Berücksichtigung der Heim- und Auswärtsmannschaften die Entfernung und die Anstoßzeit die wichtigsten Prädiktoren für die Auswärtsfanbeteiligung sind. Darüber hinaus hat die Unterstützung der Auswärtsfans einen statistisch signifikanten positiven Einfluss auf die Leistung der Mannschaft: 1.000 zusätzliche Auswärtsfans erhöhen die Wahrscheinlichkeit, dass die Auswärtsmannschaft das Spiel gewinnt oder unentschieden spielt, um 4,6 % bis 7,5 %. Diese Ergebnisse legen nahe, dass die Liga-Organisatoren bei der Spielplanerstellung die Logistik für die Fans und den potenziellen Einfluss der Anwesenheit von Auswärtsfans berücksichtigen sollten, um die sportliche Fairness zu wahren. Auf Vereinsebene unterstreichen die Ergebnisse den Wert der Förderung des Fanengagements und deuten darauf hin, dass Strategien zur Steigerung der Auswärtsbesucherzahlen zu besseren sportlichen Ergebnissen beitragen können.
Keywords: C23; Z20; 330; Sport economics; Away fan attendance; Team performance; Spatio-temporal analysis